Correlation of Self-Reported and Performance-Based Measures In Patients With Non-Traumatic Stiff Shoulder Pathologies: An Observational Study (International Journal of Physiotherapy, 2023)
Background: Self-reported measures represent patients' perspectives toward their disease, but their performance levels may vary. Performance-based measures mimic the patient's functional activity movement, which helps evaluate specific task components, including how the therapist approached the task. Both measures report the patient's functional level from the patient's or therapist's perspective. The study was done to determine the correlation between self-reported and performance-based measures outcomes in non-traumatic stiff shoulder pathologies.Method: Self-reported outcome measure scores were recorded using the Shoulder Pain And Disability Index (SPADI), Disabilities of Arm, Shoulder, and Hand (DASH), and Patient Specific Functional Scale (PSFS). Performance-based measures scores of the shoulder were given using function-related tests of the shoulder: 1) Hand to the neck, 2) Hand to scapula 3) Hand to the opposite scapula.Result: Inferential statistics were done using the Pearson correlation test, and the significance level was set at p